Structural and Electrical Properties Dependence on annealing temperature of a-Ge:Sb/c-Si Heterojunction - A. A. Shehab; H. Kh. Al-Lamy; M. H. Mustafa (Ibn Al-Haitham Journal for Pure and Applied Sciences, 2016)
In this work, we are Study the effect of annealing temperature on the structure of a-Ge films doped with Sb and the electrical properties of a-Ge:Sb/c-Si heterojunction fabricated by deposition of a-Ge:Sb film on c-Si by using thermal evaporation. Electrical properties of aGe:Sb/c-Si heterojunction include I-V characteristics in dark at different annealing temperatures and C-V characteristics and with the C-V characteristics suggest that the fabricated heterojunction was abrupt type, built in potential determined by extrapolation from 1/C2-V curve and show that the built - inpotential (Vbi) for the Ge:Sb/Si system increases with the increase of annealing temperatures